Freiheit und Pluralismus: Isaiah Berlins zentrale Ideen als Material für die heutige Philosophie - Reick, Robert (EUKLID : Europäische Kultur und Ideengeschichte. Studien, 2016)
This study firstly suggests to re-interpret BERLIN's concept of freedom by rejecting the notion of positive freedom as mis-naming. Secondly BERLIN's concept of objective pluralism is analyzed in a way that understands any value as one among other values which can come into unresolvable conflict since actors have to choose between incommensurable and incomparable values. The dissertation finally explores contemporary fields of debate around liberalism, perfectionism, and participation.